Development of Deep Learning-based Instructional Module for Enhancing Critical Thinking in Pancasila Learning - Anggrayni, M.; Asmaryadi, Ahmad Ilham; Susilawati, Wiwik Okta (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to develop a deep learning-based instructional module for enhancing critical thinking in Pancasila education at the elementary level. The Research and Development (R&D) method was employed, using the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation stages. Data were collected through interviews, observations, document analysis, and surveys, with a particular emphasis on the dimensions of validity, practicality, and effectiveness as the core framework for the data analysis technique. The module demonstrated high validity, with expert evaluations rating it